1988
DOI: 10.1007/bf02412426
|View full text |Cite
|
Sign up to set email alerts
|

Upper esophageal sphincter function in patients with Zenker's diverticulum

Abstract: Abstract.Upper esophageal sphincter function (UES) was studied in 8 patients with Zenker's diverticulum. Radiologic and endoscopic studies revealed pharyngoesophageal diverticula of varying size. No tumor or stenosis was found. Esophageal manometry showed no significant difference between patients and 8 matched controls with respect to UES resting pressure, delay of maximal UES relaxation, and maximal pharyngeal contraction. All patients exhibited a drop of the UES pressure to esophageal resting pressure durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Van Overbeek 3 stated that the pathogenesis may also be related to the individual anatomic structure, and height, of the triangle of Killian. Numerous other etiologic mechanisms have been considered of influence, including abnormalities in relaxation of the cricopharyngeal muscle and premature muscular contraction or incoordination between pharyngeal contraction and the upper esophageal sphincter, but several studies [4][5][6] suggest that they do not play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Van Overbeek 3 stated that the pathogenesis may also be related to the individual anatomic structure, and height, of the triangle of Killian. Numerous other etiologic mechanisms have been considered of influence, including abnormalities in relaxation of the cricopharyngeal muscle and premature muscular contraction or incoordination between pharyngeal contraction and the upper esophageal sphincter, but several studies [4][5][6] suggest that they do not play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal manometry has been used to decipher the etiology of ZD [ 13 ] and Migliore et al recommend surgical intervention only after manometric evaluation [ 14 ]. However, other studies showed inconsistent upper esophageal sphincter pressures with varying timing of contraction [ 15 , 16 ] suggesting that the manometry is an unreliable tool for ZD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Frieling et al described an abnormal sequence of pharyngeal and oesophageal contractions [14]. Barthelen et al proposed that there was an anatomical basis for the disease as it was due to patients having a large constrictor-cricopharyngeus space and that there was mucosal prolapse due to loss of tissue elasticity with age [15].…”
Section: Discussionmentioning
confidence: 99%